TINJAUAN LOYALITAS TAMU DI HOTEL PANGERAN PEKANBARU - Elvi Oktariani; Syofia Achnes (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Loyalty is an important thing in any industry, including in the hotel industry. There are some definition of customer loyalty, which can be concluded as “the behavior and attitude that is shown by a customer in type of repurchasings and commitments in al long term at a certain company or product”. Hotel Pangeran Pekanbaru is challenged to retain their customer to always be chosen at anytime they stay in Pekanbaru. The loyalty aspect of Hotel Pangeran Pekanbaru’s customer is described by this research. The loyalty aspects are satisfaction, emotional bonding, trust, habit and history with the company. The stages of customer loyalty were also revealed on this research. William G. Zikmund’s theory was used to analyze the loyalty aspect, while Jill Griffin’s was the main theory to analyzed the customer’s stages of loyalty. There were 100 respondents which were Hotel Pangeran Pekanbaru’s guests contributed in this research. The accidental sampling were used to choosed which guests would be the respondents to answer some questions about their loyalty. Descriptive analysis was used to analyze the research datas. Emotional bonding, trust and habit were the three main aspects that affect the customer’s loyalty, while most of the respondents were in the “advocate” stage of loyalty.Keywords : Customer loyalty, loyalty aspects, loyalty stages